EKSTROFI KANDUNG KEMIH PADA BAYI PEREMPUAAN SEBUAH LAPORAN KASUS - Nyoman Gede Prayudi (Universitas Udayana, 2014)
Three days old newborn female child with supravesical fissure; one of exstrophy bladder variant which rare to found . Physical examination on abdominal region looks a reddishbladder and normal external genital. Plain photo abdomen shows opacity in the pelviccavity to the below abdominal impress the bladder. The patients did not have surgicalreconstruction because she got cardiac abnormalities in the form of classic TOF so thatsurgery was delayed until improved cardiac performance.